KAITAN LEVERAGE, UKURAN PERUSAHAAN, ASIMETRI INFORMASI, DAN NPM TERHADAP PRAKTIK MANAJEMEN LABA - Sakagita, Marvella Andika; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to determine the correlation of leverage, firm size, information asymmetry and net profit margin on earnings management in manufacturer company registered in the Indonesia Stock Exchange in 2017-2019. The method used in the sample selection is purposive sampling method. The research was conducted on 76 companies and the data obtained were processed using SPSS Statistic 25. The result of this research shows leverage, firm size, information asymmetry and net profit margin don’t have a significant effect on the earnings management in manufacture companies.